Inkluzní fibrilární degradace cytoplazmy a ubikvitin - Bednár, B; Mandys, V (Ceskoslovenska patologie, 1993)
Cell degradation of various origin often starts with an ubiquitinization of damaged proteins and with later production of roughly fibrillar electron-microscopical inclusions. There is a strong immunohistological positivity of ubiquitin in the early intracellular phase. It tends toward an apoptotic lysis either ending with extracellular immunohistologically inert refuse of amyloid type or representing various inter-steps of the degradation process. The ubiquitinization is the most common in neurons and paraneurons. A general importance of ubiquitinization is proved by ubiquitin fibrillar inclusions which were observed in growing old tissue cultures as an expression of programmed cell death. Immunodetection of increased ubiquitin is labour-saving as compared with some classical methods detecting similar lesions particularly in neuropathology.
Keywords: fibroblasty; Inclusion Bodies; ubikvitiny; Fibroblasts; nervová tkáň; Nerve Tissue; Ubiquitins; buněčná inkluze; lidé; Cellular Senescence; stárnutí buněk; Humans; Cell Line; buněčné linie